Impact of Maternal Employment on Adolescent Personality Traits and Problem Solving Appraisal - Mehreen, Saima Arzeen, Sidra Batool, Muhammad Sajjad Shahid, Sana Nauman, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose This study investigates the impact of maternal employment on the character and problem-solving abilities of their children. As the number of women entering the workforce continues to rise, researchers have debated whether maternal employment is beneficial or detrimental to children. The quality of life for adolescents depends on their relationship with their mothers, and this relationship is a significant determinant of their wellbeing. Method: To explore this relationship, adolescents of employed and non-employed mothers were randomly selected from schools while controlling for variables such as joint family system, religion, gender, and age. The Dimensional Personality Inventory (DPI) by Mahesh Bhargava and Problem-Solving Appraisal (PSI) were used to collect data. Findings: The results show a significant difference between the adolescents of employed and non-employed mothers. The study found that the attachment between literate employed mothers and their daughters is deteriorating, but this attachment has less impact on boys than on girls. Practical Implication: Based on the findings, the paper provides suggestions for future research. Conclusion The research indicates notable dissimilarities between the personality traits and problem-solving appraisal of adolescents of working and non-working mothers. According to the findings, working mothers exhibit more efficiency and competence in managing interpersonal relationships, whereas non-working mothers demonstrate greater responsibility and better judgment skills, as well as being more capable of inspiring individuals to take action. Furthermore, there are significant variations in self-development characteristics, including self-awareness, self-efficacy, confidence in problem-solving, and integrity. Keywords: Self-control, Dimension, Attachment, Adolescents, Working and Non-working Mothers